Memory Studies in India : Texts and Contexts - Parui, Avishek,; Raj, Merin Simi, (Literature and Cultural Studies E-Books Online, Collection 2026., 2025)
This pioneering volume marks a significant contribution to memory studies in India, offering an in-depth exploration of how collective and individual memories shape and reshape identities, narratives, and historical knowledge. By addressing a diverse array of topics-from forgotten events, massacres, and monuments to public spaces and food rituals-across various epochs, the essays in this collection bring new insights into India's complex cultural history. With contributions from scholars across different stages of their academic careers, this volume not only enriches the field of memory studies but also paves the way for future research in India and beyond.